The influx of national identity: “imagined communities” on Indonesian audience in Indonesia and Malaysia frontier - Briandana, Rizki; Azmawati, Azman Azwan (Faculty of Communications Science, Dr. Soetomo University, 2021)
This study aimed to analyse the abundance of Malaysian television broadcasts’ impact on building Indonesian society’s national identity on Sebatik Island. The residents of this island have been watching Malaysian television for a long time as the primary source of communication in their daily lives. In this context, the interaction between the community and television is manifested through interpreting images and meanings. Furthermore, it becomes the basis for the building process of the community’s national identity. This was a case study with observation and focus group discussion as the method of data collection. The results showed that Malaysian television conveys the meaning and values of its nationality to the Indonesian people. This manifests a high tendency among the Sebatik residents towards Malaysia, which is considered an ideal reference of life.